2006
DOI: 10.1007/s10722-004-6130-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Tunisian Olive Tree (Olea europaea L.) Cultivars Assessed by AFLP Markers

Abstract: About 29 olive (Olea europaea L.) cultivars including oil and table olive cultivars originating from Tunisia and other Mediterranean countries, were genotyped using amplified fragment length polymorphism (AFLP) DNA markers. This technique is a rapid and efficient method for producing DNA fingerprints. Using nine AFLP primer combinations, we produced a total of 410 AFLP markers, among which 172 revealed polymorphism. The results demonstrated a high degree of polymorphism in the olive germplasm we examined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 33 publications
4
42
0
1
Order By: Relevance
“…Previously, Grati-Kamoun et al (2006) showed that the AFLP marker system was able to separate closely related olive (Olea europaea L.) accessions. Thus, our result is also in general agreement with this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Grati-Kamoun et al (2006) showed that the AFLP marker system was able to separate closely related olive (Olea europaea L.) accessions. Thus, our result is also in general agreement with this study.…”
Section: Resultsmentioning
confidence: 99%
“…The primer combinations differed in their ability to detect polymorphism within populations. Grati-Kamoun et al (2006) characterized 29 olive (Olea europaea L.) cultivars including oil and table olive cultivars originating from Tunisia and other Mediterranean countries using AFLP markers. Using nine AFLP primer combinations, they produced a total of 410 AFLP markers, among which 172 revealed polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…The olive tree has a large number of commercial cultivars with different levels of self-incompatibility (Grati-Kamoun et al, 2006). The phenological and reproductive biology of this species has been the focus of several studies aimed at identifying self-compatible cultivars and assessing rates of self-sterility (Albertini et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Owen et al, (2005) used AFLP markers to evaluate the structure of genetic diversity among common olive varieties cultivated in the Eastern Mediterranean. Additionally, AFLP analysis, as previously described and has been used in genetic variability studies for about 29 varieties (including oil and table olive varieties originating from Tunisia and other Mediterranean countries) of the genus Olea using nine AFLP primer combinations (Grati-Kamoun et al, 2006). Different studies (Busconi et al, 2003, Pafundo et al, 2005 have reported that it is possible to use AFLP markers for genotyping olive species.…”
Section: Aflps (Amplified Fragment Length Polymorphism)mentioning
confidence: 99%